Introgression profiling of F4 population derived from the cross of Zea mays × Teosinte spp. Mexicana using SSR markers - Kaur, R; Ashmita; Devi, N; Tyagi, V; Vikal, Y; Sharma, P (Plant Science Today, 2025)
To increase the production of crops together with resistance to biotic and abiotic stresses, germplasm enrichment is much more important in any breeding programme. Exploitation of Teosinte and Tripsacum, the wild relatives of maize, as the sources of novel genes to improve resiliency, adaptability and productivity in maize, has been documented. In the present study, teosinte was used in the crossing programme. The experiment material comprised 109 RILs derived from Teosinte spp. mexicana and popcorn. Using SSR markers, the introgression profiling of teosinte-derived maize F4 population (109 maize-teosinte derivatives). Morphological characterization for different parameters, i.e., days to maturity, number of cobs, number of tillers, seed rows per cob and cob length, showed significant variation among all the traits studied. The highest significant positive correlation was observed between the number of rows per cob and cob length. Introgression profiles of different lines were inferred from the consensus of genotypic and morphological data, which revealed that the marker bnlg1297 was common among the lines that exhibit a higher number of tillers and cobs. Therefore, these specific genomic regions might be associated with these traits. Thus, these results showed different parental contributions, which leads to diversification in the progenies derived from diverse crosses in maize. Further, such crosses appear crucial for producing germplasm for which breeders are looking.